2007
DOI: 10.1111/j.1365-2141.2007.06554.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the understanding and management of paroxysmal nocturnal haemoglobinuria

Abstract: SummaryParoxysmal nocturnal haemoglobinuria (PNH) has been recognised as a discrete disease entity since 1882. Approximately a half of patients will eventually die as a result of having PNH. Many of the symptoms of PNH, including recurrent abdominal pain, dysphagia, severe lethargy and erectile dysfunction, result from intravascular haemolysis with absorption of nitric oxide by free haemoglobin from the plasma. These symptoms, as well as the occurrence of thrombosis and aplasia, significantly affect patients' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 106 publications
3
88
0
1
Order By: Relevance
“…Paroxysmal nocturnal hemoglobinuria (PNH) is characterized by chronic, uncontrolled complement activation leading to intravascular hemolysis and an inflammatory prothrombotic state (1,2). The etiology of this rare hematopoietic stem cell disorder is an acquired clonal genetic deficiency of glycosylphosphatidylinositol (GPI)-anchored and GPIlinked proteins on the surface of blood cells.…”
Section: Introductionmentioning
confidence: 99%
“…Paroxysmal nocturnal hemoglobinuria (PNH) is characterized by chronic, uncontrolled complement activation leading to intravascular hemolysis and an inflammatory prothrombotic state (1,2). The etiology of this rare hematopoietic stem cell disorder is an acquired clonal genetic deficiency of glycosylphosphatidylinositol (GPI)-anchored and GPIlinked proteins on the surface of blood cells.…”
Section: Introductionmentioning
confidence: 99%
“…The involved different mutations result in the deficient synthesis of glycosylphosphatidylinositol (GPI)-anchor molecule and the resulting partial or absolute deficiency, in all blood cell lineages, of the expression of GPI-anchored membrane proteins, like CD55, CD59, CD14, CD16, CD24, CD48, among others (1,7,15,18) .…”
mentioning
confidence: 99%
“…19 PNH red blood cells can be labeled type I, II or III; type I cells have normal expression of GPI-APs, type II have partial deficiency and type III lack all GPI-APs. 20 The clinical manifestations are variable; intravascular hemolysis, thrombosis and anemia are significant, however, other symptoms may be present. 1 Schrezenmeier et al analyzed 1610 patients and showed the proportion of symptoms, such as fatigue (80%), dyspnea (64%), hemoglobinuria (62%), abdominal pain (44%), chest pain (33%) and impaired renal function (14%), with only 16% of patients having a history of thrombotic events.…”
Section: Clinical Presentationmentioning
confidence: 99%